Experimental and numerical study on the ballistic performance of ultrahigh molecular weight polyethylene laminate. Issue 10 (9th August 2021) - Zhu, Yihui; Liu, Kang; Wen, Yaoke; Cui, Guangyu; Niu, Weilong; Wang, Yongjuan; Cao, Yanfeng; Xu, Cheng
Abstract: Ultrahigh molecular weight polyethylene (UHMWPE) fiber orthogonally laid laminate is widely used in ballistic protection due to its excellent properties. Research on its response under bullet impact is meaningful for understanding the antiballistic mechanism and designing personal protection. In this article, three‐dimensional digital image correlation measurement and analysis method is applied to study the response of UHMWPE orthogonally laid laminates under the impact of pistol bullets. A corresponding smoothed particle hydrodynamics (SPH)–finite element method coupled numerical model is established to study the impact phenomenon. The bullet model is developed using the SPH method. The laminate is developed with multiple equivalent sublaminate finite element models. The experimental results show the damage mode and back‐face features of the laminate. First, the damage mode has two stages: the first stage includes a small number of layers that are penetrated on the impact surface and the second stage includes the expansion of the back‐face deformation. Second, the average maximum bulge height in three repeated experiments is 14.59 mm. Third, the average maximum velocity of the bulge apex position in experiments on the z ‐axis is 92.32 m/s. Fourth, the maximum and minimum back‐face in‐plane shear values are 0.0893 and −0.0928, respectively. Finally, the numerical results have good agreement with the experimental results and show that the compression waves mainly propagate along the x and y directions. The experimental results can provide quantifiable features for studying the impact responses of UHMWPE laminates. The numerical model could be applied to study features that cannot be measured by experiments. Abstract :